2023
DOI: 10.1136/bmjment-2023-300842
|View full text |Cite
|
Sign up to set email alerts
|

Living alone and mental health: parallel analyses in UK longitudinal population surveys and electronic health records prior to and during the COVID-19 pandemic

Abstract: BackgroundPeople who live alone experience greater levels of mental illness; however, it is unclear whether the COVID-19 pandemic had a disproportionately negative impact on this demographic.ObjectiveTo describe the mental health gap between those who live alone and with others in the UK prior to and during the COVID-19 pandemic.MethodsSelf-reported psychological distress and life satisfaction in 10 prospective longitudinal population surveys (LPSs) assessed in the nearest pre-pandemic sweep and three periods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Seropositive participants were more likely to be living alone. While it is well established that the pandemic had adverse effects on the mental health of those living alone, 40 there is less evidence on how living alone affected COVID-19 transmission and choices around protective behavior. However, a meta-analysis on household transmission found that counterintuitively those living in households with three or more contacts had higher secondary attack rates than those living in households with only one contact.…”
Section: Differences In Sars-cov-2 Seropositivity Between the Cohort ...mentioning
confidence: 99%
“…Seropositive participants were more likely to be living alone. While it is well established that the pandemic had adverse effects on the mental health of those living alone, 40 there is less evidence on how living alone affected COVID-19 transmission and choices around protective behavior. However, a meta-analysis on household transmission found that counterintuitively those living in households with three or more contacts had higher secondary attack rates than those living in households with only one contact.…”
Section: Differences In Sars-cov-2 Seropositivity Between the Cohort ...mentioning
confidence: 99%